2016
DOI: 10.1017/s1352465816000229
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Transdiagnostic Cognitive Behaviour Therapy for Anxiety and Depression in Adults: A Systematic Review and Meta-analysis

Abstract: Quality assessment of the primary studies indicated a number of methodological concerns that may serve to inflate the observed effects of transdiagnostic approaches. Although there are positive signs of the value of transdiagnostic CBT, there is as yet insufficient evidence to recommend its use in place of disorder-specific CBT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(68 citation statements)
references
References 60 publications
3
64
0
1
Order By: Relevance
“…Second, the protocol implemented is based on a transdiagnostic approach that seeks to deliver the same treatment for different clinical symptoms (all ED). Although there is a strong and supported psychopathological rationale for its use ( Harvey et al, 2004 ), as well as conclusive evidence of its efficacy and effectiveness both for traditional and online therapy ( Andersen et al, 2016 , Newby et al, 2015 , Newby et al, 2016 , Păsărelu et al, 2017 ), it may constitute a barrier to deliver more personalized contents.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the protocol implemented is based on a transdiagnostic approach that seeks to deliver the same treatment for different clinical symptoms (all ED). Although there is a strong and supported psychopathological rationale for its use ( Harvey et al, 2004 ), as well as conclusive evidence of its efficacy and effectiveness both for traditional and online therapy ( Andersen et al, 2016 , Newby et al, 2015 , Newby et al, 2016 , Păsărelu et al, 2017 ), it may constitute a barrier to deliver more personalized contents.…”
Section: Discussionmentioning
confidence: 99%
“…Considering MM or HQ can have distinct mechanisms of action on the effects of depression versus anxiety [24,62], it is suggested that speci c interpretations can be made regarding different modes of intervention as applied to depression and anxiety, respectively. Besides, meta-analysis suggested that although there are positive signs of the value of transdiagnostic CBT for anxiety and depression, there is as yet insu cient evidence to recommend its use in place of disorder-speci c CBT [63]. Thus, comparison of transdiagnostic-based versus disorder-speci c HQCT and MBCT is worthy of further investigation.…”
Section: Limitations and Conclusionmentioning
confidence: 99%
“…Puede también asociarse a otras barreras, como la distancia (p.ej., personas que viven en zonas rurales) o la falta de profesionales cualificados. Una forma de terapia emergente, desarrollada especialmente durante la última década, es la TCC aplicada a través de internet (iTCC) (para una revisión, véase Andersen, 2016). La iTCC posee ciertas ventajas potenciales sobre la TCC aplicada cara-a-cara, tales como facilitar el acceso físico al tratamiento, reducir el coste económico, minimizar el estigma, reducir el tiempo de atención del terapeuta, maximizar la relación coste-efectividad, mejorar el apoyo continuado al paciente y, en último término, incrementar en la población el acceso a los tratamientos psicológicos basados en la evidencia.…”
Section: Introductionunclassified